Sequential Imaging in Patient With Suspected Menière's Disease Identifies Endolymphatic Sac Tumor. Issue 9 (October 2018) - Kirsh, Elliana R.; Kozin, Elliott D.; Knoll, Renata M.; Wong, Kevin; Faquin, William; Reinshagen, Katherine L.; Kieff, David; Rauch, Steven D.; Jung, David H.
Abstract : Objective: The standard evaluation of patients with suspectedMenière's disease (MD) includes initial imaging to rule out tumors of the temporal bone. Few guidelines, however, advocate sequential imaging. We propose that sequential imaging may reveal other etiologies of auditory and vestibular symptoms as demonstrated in a patient with an endolymphatic sac tumor that was originally diagnosedMenière's after initial imaging. Patients: One patient with MD and initially unremarkable imaging. Repeat imaging several years after diagnosis after additional symptoms demonstrated interval development of an endolymphatic sac tumor (ELST). Interventions: Resection of endolymphatic sac tumor. Main Outcome Measures: 1) Audiometry, 2) temporal bone imaging, and 3) otopathology Results: A 45-year-old man with diagnosis of asymmetric sensorineural hearing loss and intermittent vertigo underwent temporal bone magnetic resonance imaging that did not demonstrate any causative lesions. After an episode of sudden sensorineural hearing loss 4 years after initial presentation, repeat imaging was obtained. Magnetic resonance imaging and surgical resection confirmed diagnosis of ELST. The patient had no history of von Hippel-Lindau disease. Conclusions: A patient with a longstanding diagnosis of MD demonstrated interval development of an ELST. While ELSTs are rare, the study raises the question regarding whether interval imaging is indicated in patients with MD.